(untitled) (diségno, 2020)
“A buon intenditor poche parole”; “A word to the wise (is sufficient)”; “À bon entendeur, demi-mot (suffit)”; “mezza parola”: in practically every language (and in many dialects) there is a saying of analogous meaning. The meaning is clear: to communicate effectively with those who are experts, with those who are well versed in something and have a precise competence, very little is needed. No need to get lost in long speeches or detailed descriptions. ʻA half word’ is enough for the wise (read more).